Prevalence of high N-terminal prohormone of brain natriuretic peptide levels and associated factors among community-dwelling older adults aged over 75 years (The SONIC study): a cross-sectional study - Saya Terada; Kayo Godai; Mai Kabayama; Michiko Kido; Yuya Akagi; Hiroshi Akasaka; Yoichi Takami; Takeshi Nakagawa; Saori Yasumoto; Yasuyuki Gondo; Kazunori Ikebe; Yasumichi Arai; et al. (BMC Research Notes)
Abstract Objectives Considering the heart failure (HF) pandemic, numerous older adults in the community may exhibit potential cardiac overload or asymptomatic HF without apparent HF diagnosis. This study aimed to examine the distribution of serum N-terminal prohormone of brain natriuretic peptide (NT-proBNP) levels in community-dwelling old age adults aged ≥ 75 years, and to investigate the associated factors for each NT-proBNP classification. Results A cross-sectional analysis revealed that 52.0% of 611 participants had NT-proBNP ≥ 125 pg/mL. Multinomial logistic regression analysis showed that female sex, older age (80s and 90s), and uncontrolled high blood pressure were significantly associated with 125 ≤ NT-proBNP < 300 pg/mL, while older age (80s and 90s), coronary artery disease, atrial fibrillation, and renal dysfunction were significantly associated with NT-proBNP ≥ 300 pg/mL. Independent association between higher salt intake and NT-proBNP ≥ 300 pg/mL was also observed. Appropriate management of common HF risk factors, such as uncontrolled high blood pressure and high salt intake, is crucial to prevent the progression of overt HF.